2016
DOI: 10.2147/mder.s103102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and safety of powered exoskeleton-assisted walking in patients with spinal cord injury: systematic review with meta-analysis

Abstract: Background: Powered exoskeletons are designed to safely facilitate ambulation in patients with spinal cord injury (SCI). We conducted the first meta-analysis of the available published research on the clinical effectiveness and safety of powered exoskeletons in SCI patients. Methods: MEDLINE and EMBASE databases were searched for studies of powered exoskeleton-assisted walking in patients with SCI. Main outcomes were analyzed using fixed and random effects meta-analysis models. Results: A total of 14 studies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
230
2
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(262 citation statements)
references
References 39 publications
9
230
2
21
Order By: Relevance
“…Interestingly, these studies revealed significant interspecies differences in the mechanisms of corticospinal tract regeneration during motor recovery when comparing rodents to primates and humans. Finally, combinatorial and holistic approaches that incorporate rehabilitation, pharmacology, neuromodulation (Moraud et al, 2016; Wenger et al, 2016) as well as emerging technologies like the exoskeleton (Gad et al, 2015; Miller et al, 2016) raise hopes that meaningful, functional recovery is achievable in the foreseeable future.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these studies revealed significant interspecies differences in the mechanisms of corticospinal tract regeneration during motor recovery when comparing rodents to primates and humans. Finally, combinatorial and holistic approaches that incorporate rehabilitation, pharmacology, neuromodulation (Moraud et al, 2016; Wenger et al, 2016) as well as emerging technologies like the exoskeleton (Gad et al, 2015; Miller et al, 2016) raise hopes that meaningful, functional recovery is achievable in the foreseeable future.…”
Section: Resultsmentioning
confidence: 99%
“…Незважаючи на значну біомедичну та соціально-економічну вагу про-блеми спінальної травми [1][2][3], тривалу зацікав-леність наукової спільноти питаннями віднов-лення функції ураженого спинного мозку [4][5][6][7], багато питань цього кола залишаються невивче-ними. Травма спинного мозку перебуває в аван-гарді сучасної біо технологічної галузі, до її вирі-шення залучаються найновіші розробки біонічно-го (нейропротезування, екзоскелетування) [8][9][10], біогенного (тканинна нейроінженерія) [11][12][13][14] та комплексного [15] характеру. Одними із най-складніших, з патофізіологічної точки зору, пи-тань є механізми формування синдрому спас-тичності, який виявляють у 45-78 % спінальних хворих [16][17][18][19].…”
unclassified
“…In the article “Clinical effectiveness and safety of powered exoskeleton-assisted walking in patients with spinal cord injury: systematic review with meta-analysis”, published in the March issue of Medical Devices: Evidence and Research , Miller et al1 present a meta-analysis of the clinical effectiveness and safety of powered exoskeletons for spinal cord injury (SCI) patients. A close examination of this article shows surprising coincidences, in that two primary studies (references 25 and 33 in the reference list) report the same proportions and 95% confidence intervals (CIs) of subjects able to ambulate with an exoskeleton without assistance (Figure 2 of the study), and two different primary studies (references 26 and 28) report the same mean and 95% CIs for the distance (in meters) walked in a 6-minute walk test (Figure 4 of the study).…”
mentioning
confidence: 99%
“…In fact, nine of the 14 studies included in the meta-analysis by Miller et al1 can be assigned to three groups of studies that may contain duplicate patient information: New York City: references 23, 27, 32, and 34Philadelphia: references 25, 33, and 35Atlanta: references 26 and 27…”
mentioning
confidence: 99%
See 1 more Smart Citation